Assessment of Pro Hepcidin and Related with Iron Profile on Hemodialysis Men Patients (Baghdad Science Journal, 2016)
Patients with renal failure in the final stages undergo the treatment by hemodialysis. Hemodialysis is used to reinstate the intracellular and extracellular fluid environment, by propagation of molecules in solution through a semipermeable membrane along an electrochemical concentration gradient. Blood catching in the dialysis machine and the recurrent phlebotomy may lead to losing about 1-3 g of iron per year. Prohepcidin hormone is an acute phase protein (type II) that plays a major role in the systemic iron irregularities as it is a mediator of anemia in inflammation and regulator of iron metabolism. This study aims to evaluate the effect of hemodialysis on iron hemostasis and its relationship with prohepcidin as an inflammatory marker. This study includes forty four adult male patients with end-stage renal failure (in pre and post –treated) by means of chronic hemodialysis-HD with mean age (53.27 ± 13.76 years). The following biochemical investigations have been studied: Prohepcidin, Iron, Ferritin, Transferrin, Total Iron-Binding Capacity (TIBC), The Unsaturated Total Iron Binding Capacity (UIBC), and transferrin saturation (TAST).Decrement of Prohepcidin level on hemodialysis patients in post dialysis with non-significantly compared to pre dialysis, while iron and ferritin was increment in post treated than pre- treated with non-significantly.Hemodialysis affects Prohepcidin levels as it was long duration and Glomerular Filtration rate GFR (cock croft equation) and prohepcidin level affect the iron profile related with the iron store depletion.